Three generations of women, three generations of care. Notes from a moral ethnography - Martín Palomo, María Teresa (Cuadernos de Relaciones Laborales, 2013)
Caregiving in families has become a topic of great interest in the context of the increasing participation of women in paid work, atributtions reduce the welfare state and the aging population in modernized societies. This article presents some reflections on an ethnographic research conducted in the province of Seville (Spain), in which we study how interact different dimensions (material, moral and emotional) operating in the intergenerational transmission of knowledge and skills about care provided in familiar environments.